2015
DOI: 10.1137/140988218
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Error Estimates of Spectral Petrov--Galerkin and Collocation Methods for Initial Value Problems of Fractional Differential Equations

Abstract: We present optimal error estimates for spectral Petrov-Galerkin methods and spectral collocation methods for linear fractional ordinary differential equations with initial value on a finite interval. We also develop Laguerre spectral Petrov-Galerkin methods and collocation methods for fractional equations on the half line. Numerical results confirm the error estimates. Introduction.Numerical methods for fractional differential equations have been investigated for decades; see, e.g., [8,12,33]. However, spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 38 publications
0
34
1
Order By: Relevance
“…When solving these FDEs, the singularity requires special attention to obtain the expected high accuracy. Several approaches have been proposed to deal with the weak singularity, such as using adaptive grids (nonuniform grids) to keep errors small near the singularity [18,44,51], or employing non-polynomial basis functions to include the correct singularity index [2,14,52], or using the correction terms to remedy the loss of accuracy and recover high-order schemes [18,30,46,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…When solving these FDEs, the singularity requires special attention to obtain the expected high accuracy. Several approaches have been proposed to deal with the weak singularity, such as using adaptive grids (nonuniform grids) to keep errors small near the singularity [18,44,51], or employing non-polynomial basis functions to include the correct singularity index [2,14,52], or using the correction terms to remedy the loss of accuracy and recover high-order schemes [18,30,46,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…For anomalous transport, it has been shown that fractional ordinary/partial differential equations FODEs/FPDEs are the most tractable models that rigorously code memory effects, self-similar structures, and power-law distributions [26,34,15,24,27]. In addition to finite difference and higher-order compact methods [20,25,33,9,5,39,3,16,38,40], a great progress has been made on developing finite-element methods [23,10,28] and spectral/spectral-element methods [31,37,36,35,4,6,42,22,43,14,41,32,19,12] to obtain higher accuracy for FODEs/FPDEs.…”
mentioning
confidence: 99%
“…(2) Use some nonpolynomial (or singular) basis functions or collocation spectral methods to capture the singularity of the solutions of (1.1), see [1], [5], [13], [14], [34], [27], [59], [63], [67]. (3) Separate the solution into two parts: smooth and nonsmooth parts.…”
mentioning
confidence: 99%